Chinese Muslims in Malaysia : Islam, culture and identity - Mahmud, Mek Wok (Pustaka Yamien Sdn. Bhd., 2020)
This book is a priceless contribution to the literary world on the Malaysian Chinese Muslims’ contributions in nation building in Malaysia. There is no doubt that there are numerous treatises written on Chinese Muslims in various disciplines and objectives. However, what distinguishes this book from the other treatises is its multi-disciplinary approach. It tries to address several themes in a single volume. Among others, this includes: (a) The Malaysian Chinese Muslims’ sociological and legal problems; (b) The Chinese Muslims’ contributions to the economic development and the proposed solutions to improve its low-income groups; (c) The Chinese Muslim NGOs’ contributions to religious harmony in a multi-religious and cultural society; and (d) The ideological expectations on the Chinese Muslims’ contributions through their practicing of Islamic values and teachings on their families, the communities and nation.